Ultrasound Frequency Of KUB Stones In Patients With Flank Pain - Asif, Amen; Zulfiqar, Taiba; Ali, Abid (Medical Science Journal for Advance Research, 2022)
Aims and objectives: To find out the frequency of kUB stones in patients with flank pain. Methods: This prospective cross-sectional study was done at the Radiology Department of DHQ Hospital, Gujrat. It includes a total 61 patients who presented with flank pain. The age range of patients was between 21 to 75 years and included 35 males and 26 females. SPSS was then used for Statistical analysis. Frequency of renal tract stones was calculated. Results: - Out of 61 patients who presented with flank pain, stones were present in 45 (73.7%) patients. 17( 27.9%) stones were seen in right kidney, 12(19.7%) stones were seen in left kidney,13(21.3%) in right ureter and 3(4.91%) in left ureter. Conclusion: - Sonography is an excellent modality with many benefits for diagnosing kidney stones it is non-ionizing radiation free, relatively inexpensive, widely available, and simple to use, with a high diagnostic effectiveness. It is concluded patients that are reported with flank pain have kidney stones.